2011
DOI: 10.3758/s13423-011-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-verbal number acuity correlates with symbolic mathematics achievement: But only in children

Abstract: The process by which adults develop competence in symbolic mathematics tasks is poorly understood. Nonhuman animals, human infants, and human adults all form nonverbal representations of the approximate numerosity of arrays of dots and are capable of using these representations to perform basic mathematical operations. Several researchers have speculated that individual differences in the acuity of such nonverbal number representations provide the basis for individual differences in symbolic mathematical compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
186
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(211 citation statements)
references
References 19 publications
16
186
4
5
Order By: Relevance
“…If we assume that w correctly indexes ANS acuity, and if we only had recourse to this measure in our correlation analyses, we would be led to conclude that the data do not support the existence of a relationship between ANS acuity and arithmetic proficiency (as Castronovo & Göbel, 2012;Gilmore et al, 2011;Inglis et al, 2011;Price et al, 2012). On ASSESSING THE APPROXIMATE NUMBER SYSTEM the other hand, if we consider that CV is an adequate index of ANS acuity, we would have to conclude the opposite, as we found a significant correlation between CV and our arithmetic measure (as Mejias & Schiltz, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…If we assume that w correctly indexes ANS acuity, and if we only had recourse to this measure in our correlation analyses, we would be led to conclude that the data do not support the existence of a relationship between ANS acuity and arithmetic proficiency (as Castronovo & Göbel, 2012;Gilmore et al, 2011;Inglis et al, 2011;Price et al, 2012). On ASSESSING THE APPROXIMATE NUMBER SYSTEM the other hand, if we consider that CV is an adequate index of ANS acuity, we would have to conclude the opposite, as we found a significant correlation between CV and our arithmetic measure (as Mejias & Schiltz, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Several recent studies have shown that individuals' ANS acuities are correlated with achievement in symbolic mathematics (e.g. Gilmore, McCarthy & Spelke, 2010;Libertus, Feigenson & Halberda, 2011;Mazzocco, Feigenson & Halberda, 2011a, 2011b; but see Inglis, Attridge, Batchelor & Gilmore, 2011;Price, Palmer, Battista & Ansari, 2012), lending credence to the suggestion that the ANS is implicated in the development of symbolic mathematics competence.…”
mentioning
confidence: 85%
“…When presenting numerical comparison tasks (where participants are shown two dot arrays and asked to determine which is more numerous), some researchers have permitted participants to decide how long to study the stimuli before reaching a judgement (e.g., Inglis et al, 2011;Pica et al, 2004), whereas others have displayed the stimuli for a fixed period. Among those who have used fixed stimuli durations, some have displayed stimuli for as little as 200ms (e.g., whereas others have used up to 2500ms (e.g., , and some researchers have used different stimuli durations for different participants within the same experiment (e.g., Mazzocco, Feigenson & Halberda, 2011b).…”
mentioning
confidence: 99%
“…Bonny & Lourenco, 2013;Castronovo & Göbel, 2012;Halberda, Ly, Willmer, Naiman, & Germine, 2012;Inglis et al, 2011;Libertus et al, 2011Libertus et al, , 2012Lyons & Beilock, 2011;Mazzocco et al, 2011a;Piazza et al, 2010;Price et al, 2012;Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013). It makes the INDEXING THE APPROXIMATE NUMBER SYSTEM 5 theoretical assumption that the ANS operates according to the Weber-Fechner law (e.g.…”
mentioning
confidence: 99%